Spatial Features of Covid-2019 Diffusion in Russian Regions: the View of the Transport Geographer - Sergey A. Tarkhov (Geography, Environment, Sustainability)
The purpose of the article was to analyze the spatial spread of COVID-2019 in the regions of Russia in comparison with European countries in 2020–21 from a transport-geographical point of view. The article reveals interregional differences in the number of cases and the incidence (sickness) rate as of August 1, 2021 for individual regions of Russia. The coronavirus entered two Russian regions directly from Wuhan (China) and eight regions from Northern Italy. The first virus carriers arrived by air transport, which was the main means of spreading the epidemic. Spatial diffusion of COVID-2019 in Russia was extremely uneven with epicenters in the large cities. In the early stages the coronavirus spread in an exclusively hierarchical way through the established extensive air communication system. The later stages of its spread were characterized by mixed diffusion with the dominance of the hierarchical form. COVID-2019 has six gradations of the incidence (sickness) rate expressed in the number of cases per 1 million inhabitants: very high (more than 140), high (90–140), moderate (70–90), medium (45–70), low (20–45), very low (6–20). For the Russian regions the most typical were low (51 regions) and medium (20 regions) incidence rates – 60% and 23.5% (84% in total), respectively. The incidence rate, according to official data from Rospotrebnadzor (Russian Agency of Consumer Supervision), is 38% lower than in European countries. The average number of Russian cases in the first seven months of 2021 was 1.8 times more than for the entire 2020.